2018
DOI: 10.1111/aas.13207
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nasotracheal tube depth in response to head and neck movement in children

Abstract: A change in the position of the tracheal tube tip in the trachea depends mainly on changes in t-length during paediatric dental surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…After choosing the appropriate tube diameter, the nasotracheal tube should be inserted into the appropriate position as head and neck surgery involves various neck positions and it is difficult to approach and manage the tube during the surgery. The changes in neck position can cause changes in the tracheal length [32], and the direction of tube displacement is usually cephalad with head extension and caudal with head flexion, although head extension caused unintended right main stem intubation in 4% of patients in a previous study [4]. Neck flexion and extension resulted in a tube displacement of more than 10 mm in more than 70% of patients in another study [17].…”
Section: Plos Onementioning
confidence: 90%
“…After choosing the appropriate tube diameter, the nasotracheal tube should be inserted into the appropriate position as head and neck surgery involves various neck positions and it is difficult to approach and manage the tube during the surgery. The changes in neck position can cause changes in the tracheal length [32], and the direction of tube displacement is usually cephalad with head extension and caudal with head flexion, although head extension caused unintended right main stem intubation in 4% of patients in a previous study [4]. Neck flexion and extension resulted in a tube displacement of more than 10 mm in more than 70% of patients in another study [17].…”
Section: Plos Onementioning
confidence: 90%
“…Yamanaka et al investigated the airway length changes during nasotracheal intubation in pediatric patients. They found that the head flexion-to-extension positional changes caused a slight change in the length of the pharyngeal cavity, the authors asserted that the cuff position was also likely to be changed [23]. Hartrey et al found that the magnitude of movement was smaller with nasotracheal, compared to that with orotracheal tubes [19].…”
Section: Discussionmentioning
confidence: 99%
“…The reinforced ETT was equipped with a spiral hose on the inner wall and a spring inside the spiral hose, which made the tube soft and flexible, as well as resistant to bending and compression. The trachea was a cylindrical tube, supported by “C” shaped tracheal cartilage, connected by a cricoid ligament, and surrounded by smooth muscle tissue and fibrous connective tissue to form a membranous wall ( 5 ). The trachea’s anatomical characteristics allowed it to be flexible enough to accommodate the head movements.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hartrey and Kestin ( 23 ) discovered no difference in ETT displacement between oral and nasal intubations during head extension or flexion in adults. Another study ( 5 ) reported that the trachea length and the distance between the nares and the vocal cords were both changed during head extension or flexion in children. And the displacement of the ETT depended mainly on the changes in trachea length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation